Peningkatan Pemahaman dan Keterampilan Siswa SD dalam Menggunakan Mikroskop untuk Pembelajaran Materi Biologi - Irma Rahayu; Suharno Suharno; Fawuni G.A.G. Rumbrawer; Aryanti S. Pallo; Annisa Al FAdillah Ruhani; Wilda Z. Muhhida (Bakti Hayati: Jurnal Pengabdian Indonesia, 2026)
The effectiveness of the learning system for elementary school students is crucial in enhancing critical thinking skills, curiosity, and basic skills, including in science education. Microscopes, as learning tools in biology and science, are essential in enhancing students’ understanding of the subject matter. The objective of this activity is to improve elementary school students’ understanding and skills in using microscopes as a tool for learning biology. The methods used included training and hands-on practice with microscopes in the Basic Biology Laboratory of the Department of Biology at the Faculty of Mathematics and Natural Sciences, Cenderawasih University, Jayapura. The participants were 35 students from Papua Harapan Elementary School. The results of the activity showed that before the training, only 15% of students were able to use microscopes properly and correctly, whereas after the training, the level of proficiency in using microscopes increased to 83%. In addition, student interest in learning biology through observation using microscopes reached 85%. This activity successfully improved students’ understanding of the parts, functions, and proper use of microscopes and provided a learning experience that was more interactive and contextual. Thus, training in the use of microscopes can be an effective strategy in supporting practical-based science learning at the elementary school level.